Analyze and Compare the Microplastic Pollution in the Water Samples at Han River Estuary (Da Nang) - Thi Thanh Hoai, Nguyen; Le Dang Khoi, Ta; Trung Son, Le; Thi Thom, Dang; Bich Ngoc, Nguyen; Thu Van, Vu; Huong, Tran Thi Thu (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 1, 2025)
The aim of this is study to analyze and compare the amount of microplastics in the surface water and water column samples at Han River estuary (Da Nang) in the rainy season 2023. Sixteen water samples (eight water column samples and eight surface water samples) were collected and analyzed to determine the quantity, shape, color, size, and polymer forms of microplastics. The results showed that microplastics were present in almost all samples and the column water samples have the tendency of pollution with higher densities. Microplastic pollution between two group samples was not consistent ranging from 49 to 489 particles/L in surface water and from 95 to 334 particles/L in column water samples. Location DN6 recorded the highest values ​​in both samples with 489 and 334 particles/L in surface water and column water, respectively. Microfragment predominates with 60.13% in both samples. Sequently, microfibers observed account for 36 and 33,33%, respectively. The remaining shapes range from the lowest of 0.57% (surface water samples) to 5.17% (water column samples). The white color predominances and found of 45 and 52.3% for surface water and water column samples, respectively. The second most popular color is blue, followed by green, red and several other colors. The microplastic with size in 50-150 μm accounts for the highest proportion 665 and 715 particles/L, respectively. Similarly, the large sizes in 300 - 500 μm account for the lowest proportion, only reaching total values of 90 and 80 particles/L, respectively. FTIR results showed that PET (Polyethylene Terephthalate) polymer has the highest density in both two samples with 750 and 310 particles/L, followed by nylon with values of 140 and 175 particles/L, respectively. The remaining polymers such as Cellophane, Polystyrene standard, Teflon, Fluoropolymer, Urea fomaldehyde etc., account for a fairly low proportion and it is different between two groups of samples.